Age-depending peculiarities of ultrastructural myocardium changes caused by experimental hyperuricemia and its combination with hypercholesterolemia - O. Gladii; Ya. Bodnar; A. Gudyma; S. Trach Rosolovska (Kazimierz Wielki University, 2017)
Gladii O., Bodnar Ya., Gudyma A., Trach Rosolovska S. Age-depending peculiarities of ultrastructural myocardium changes caused by experimental hyperuricemia and its combination with hypercholesterolemia. Journal of Education, Health and Sport. 2016;6(11):584-591. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.198743 http://ojs.ukw.edu.pl/index.php/johs/article/view/4055       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.11.2016. Revised 22.11.2016. Accepted: 30.11.2016.   UDC 616.127-091.8-02:616.153.857/.922]-092.9   age-depending peculiarities of ultrastructural myocardium changes caused by experimental hyperuricemia and its combination with hypercholesterolemia   Olena Gladii, Yaroslav Bodnar, Arsen Gudyma, Svitlana Trach Rosolovska   State Higher Educational Establishment "Ternopil I.Ya.Horbachevsky State Medical University", Ternopil, Ukraine   Summary Ultrastructural myocardial changes are the first signs that let characterizing morphological features of various pathological processes morphogenesis, including metabolic cardiomyopathy. It was defined that in animals of pubertal period hyperuricemia and its combination with hypercholesterolemia led to myocardial hyperfunction, which manifested mainly by hyperplasia of different cellular ultrastructures. Among adult animals in modelled metabolic deviations could be noted degenerative myocardial changes that appeared as partial or total organelles destruction. Key words: myocardium, hyperuricemia, ultrastructure, experiment.